2001
DOI: 10.1046/j.1365-2699.2001.00580.x
|View full text |Cite
|
Sign up to set email alerts
|

The biogeographical relations of the frogs and snakes of Sundaland

Abstract: Aim We seek to relate the present distributions of frogs and snakes of Sundaland and the known geological history of the region. Location From the Isthmus of Kra to Java and Sulawesi. Methods We relate the known ecological requirements of frogs and snakes to their geographical distributions and information on geological history. Results Microhabitat requirements for larvae of various groups of frogs are strong predictors of the breadth of their geographical distributions. At the species level, the frog faunas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
116
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(141 citation statements)
references
References 28 publications
(39 reference statements)
10
116
0
4
Order By: Relevance
“…This estimate does not contradict the idea that Mindanao became aerial about 25-30 MYBP in the late Oligocene (Brown and Alcala, 1994), but the route of faunal invasion remains unclear (Inger, 1999). Inger and Voris (2001) showed that disjunction of the Malay Peninsula from Borneo by the South China Sea (Fig. 1) occurred once about 5 MYBP in the early Pliocene.…”
Section: Evolutionary History Of Leptobrachiummentioning
confidence: 99%
See 2 more Smart Citations
“…This estimate does not contradict the idea that Mindanao became aerial about 25-30 MYBP in the late Oligocene (Brown and Alcala, 1994), but the route of faunal invasion remains unclear (Inger, 1999). Inger and Voris (2001) showed that disjunction of the Malay Peninsula from Borneo by the South China Sea (Fig. 1) occurred once about 5 MYBP in the early Pliocene.…”
Section: Evolutionary History Of Leptobrachiummentioning
confidence: 99%
“…Their ecology led Inger and Voris (2001) to associate them with Pleistocene dispersal between the Malay Peninsula and Borneo, while questioning their absence on Sumatra. The presence of L. hendricksoni on Sumatra is now confirmed, and its unique ecology does not seem to be related to Pleistocene dispersal.…”
Section: Evolutionary History Of Leptobrachiummentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, regional processes (isolation, speciation) might contribute to geographic restrictions of several species, leading to variation in overlap values. Inger and Voris (2001) and Inger and Stuebing (2005) categorized the Sarawak frogs into 2 groups based on habitat utilization: i) town or village species (Hylarana erythraea (green paddy frog) and Amnirana nicobariensis (cricket frog), and ii) forests or forest edge species, which were further divided into inland hill species (category III: P. signata, P. picturata, A. luctuosa, C. raniceps) and species confined to coastal lowlands and swamp areas (Category II: P. baramica, P. glandulosa, and P. laterimaculata). However, there has been little study of microhabitat utilization by Sarawak frogs, except for studies on microhabitat utilization by Sarawak tadpoles by Inger (1985), and frogs of the Sarawak highlands (Zainudin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…É sabido que existe um importante efeito de ilha em populações que ficam isoladas em alopatria. (Carvalho et al, 2007, Brown & Lomolino, 2000Inger & Voris, 2001, Quammen, 2008 O estudo osteológico abre a possibilidade de comparar a diferenciação osteológica dos diversos grupos dentro dos Gymnophthalmidae de maneira que auxiliem no entendimento do desenvolvimento e das relações filogenéticas desse grupo.…”
Section: Considerações Filogenéticas E Zoogeográficasunclassified